Estimates of heat and moisture over the Indian monsoon trough zone during monsoon 1979 - KULKARNI, PL (MAUSAM, 1986)
Southwest monsoon in 1979 had many unique features, It was largely a deficient monsoon year. Generally the monsoon was weak in the month of July and then there was a prolonged break after the middle of August. During this year the differences in the estimates of mass and heat fluxes in lower and middle troposphere of the monsoon trough area are studied in comparison to the normal monsoon conditions based on 20 years data, 1951 to 1970.